ML364 exerts the broad-spectrum antivirulence effect by interfering with the bacterial quorum sensing system - Zhang, Youwen; Dong, Limin; Sun, Lang; Hu, Xinxin; Wang, Xiukun; Nie, Tongying; Li, Xue; Wang, Penghe; Pang, Pengbo; Pang, Jing; Lu, Xi; Yao, Kaihu; et al. (Frontiers in Microbiology, 2022)
Antivirulence strategy has been developed as a nontraditional therapy which would engender a lower evolutionary pressure toward the development of antimicrobial resistance. However, the majority of the antivirulence agents currently in development could not meet clinical needs due to their narrow antibacterial spectrum and limited indications. Therefore, our main purpose is to develop broad-spectrum antivirulence agents that could target on both Gram-positive and Gram-negative pathogens. We discovered ML364, a novel scaffold compound, could inhibit the productions of both pyocyanin of Pseudomonas aeruginosa and staphyloxanthin of Staphylococcus aureus. Further transcriptome sequencing and enrichment analysis showed that the quorum sensing (QS) system of pathogens was mainly disrupted by ML364 treatment. To date, autoinducer-2 (AI-2) of the QS system is the only non-species-specific signaling molecule that responsible for the cross-talk between Gram-negative and Gram-positive species. And further investigation showed that ML364 treatment could significantly inhibit the sensing of AI-2 or its nonborated form DPD signaling in Vibrio campbellii MM32 and attenuate the biofilm formation across multi-species pathogens including Pseudomonas aeruginosa, Escherichia coli, Klebsiella pnenmoniae and Staphylococcus aureus. The results of molecular docking and MM/GBSA free energy prediction showed that ML364 might have higher affinity with the receptors of DPD/AI-2, when compared with DPD molecule. Finally, the in vivo study showed that ML364 could significantly improve the survival rates of systemically infected mice and attenuate bacterial loads in the organs of mice. Overall, ML364 might interfere with AI-2 quorum sensing system to exert broad-spectrum antivirulence effect both in vitro and in vivo.